A biopolymer functionalized two-dimensional WS2@TiO2 nanocomposite for in vitro biomedical and photocatalytic applications: facile synthesis and characterization. Issue 14 (10th March 2023) - Kasinathan, Kasirajan; Marimuthu, Karunakaran; Samayanan, Selvam; Yim, Jin-Heong
Abstract : Dye and microorganism-containing industrial wastewater have harmed both the environment and human health. Multifunctional nanomaterials are highly urgent. So, CS/WS2 @TiO2 NCs have potential candidates for biological and environmental applications. Abstract : Organic dyes and microorganisms in industrial wastewater have harmed both the environment and human health. In this present study, the in vitro biological and photocatalytic properties of a synthesized biogenic chitosan functionalized WS2 @TiO2 hybrid nanocomposite (NC) are investigated. The chitosan-functionalized WS2 @TiO2 hybrid nanocomposite (NC) was synthesized hydrothermally. Its microstructure and compositional properties were studied. The antibacterial activity against Staphylococcus aureus, and Bacillus subtilis (Gram-positive) and Klebsiella pneumoniae, and Escherichia coli (Gram-negative) was evaluated. The NC exhibits the highest antibacterial activity against K. pneumoniae at bacterial inhibition zones of 27 mm. It also showed remarkable anticancer effects in MCF-7 cells (cell inhibition of 74% at 100 μg mL −1 ). The biocompatibility of the composite was tested against the Vero (kidney epithelial) cell line. The results suggest that the NC had no obvious cytotoxicity. Also, the NC showed good photocatalytic performance (degradation rate of 89.43% at 150 min; K = 0.0175 min −1 ). The results suggest that chitosan functionalized WS2 @TiO2 NCs are a potential candidate for biological and environmental applications.